California's plan to decarbonize electricity omits key greenhouse gas emissions - Marie-Odile P. Fortier; Amir Sharafi; Alyssa R. Pfadt-Trilling; Samuel A. Markolf (Energy Policy, 2026)

Spatio-temporal modeling of PM2.5 exposure in California's San Joaquin Valley using a community sensor network - Kate DeMarsh; Alec M. Chan-Golston; Zeyi Moo; Peizhi Hao; Yaying Wang; Kimberly Valle; Sandie Ha; Asa Bradman; Tim Tyner; Samuel Markolf; Xuan Zhang (Journal of Environmental Management, 2026)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Infrastructure and the environment in the Anthropocene - Mikhail V. Chester; Samuel Markolf; Braden Allenby (Journal of Industrial Ecology, 2019)
For centuries, man‐made infrastructure has been viewed as separate from natural systems. Yet in the past few centuries, as the scale and scope of human activities have dramatically increased, there is accumulating evidence that natural systems are becoming increasingly, and in some cases entirely, managed by humans. The dichotomy between infrastructure and the environment is narrowing, and natural systems are increasingly becoming human design spaces. This is already apparent with the management of hydrologic systems for urban water supply, wildlife, agriculture, forests, and even the atmosphere, and we can expect management of the environment to become more so as human activities grow. Yet our infrastructure largely remains obdurate. They are designed to last for long times even as changes in the environment and technology accelerate. As such, our current infrastructure paradigms fail at the level of the complex, integrated systems and behaviors that characterize the Anthropogenic Earth. Infrastructure in the future will need to be designed for adaptive capacity and the complexities associated with techno‐environmental systems.

Adaptation frameworks used by US decision-makers: a literature review - Samuel A. Markolf; Kelly Klima; Terrence L. Wong (Environment Systems and Decisions, 2015)